Review of rigid fruit and vegetable picking robots - Zhao, Yuxia; Wan, Xuefeng; Duo, Huixiao (International Journal of Agricultural and Biological Engineering, 2023)
The important indicators to measure the goodness of rigid fruit and vegetable picking robot have two aspects, the first is the reasonable structural design of the end-effector, and the second is having a high precision positioning recognition method. Many researchers have done a lot of work in these two aspects, and a variety of end-effector structures and advanced position recognition methods are constantly appearing in people's view. The working principle, structural characteristics, advantages and disadvantages of each end-effector are summarized to help us design better fruit and vegetable picking robot. The authors start from the rigid fruit and vegetable picking robot grasping methods, separation methods, and position recognition methods, firstly introduce three different grasping methods and the characteristics of the two separation methods, then introduce the under-driven picking robot developed on the basis of the traditional rigid picking robot, then explain the single special, multi-feature, and deep learning location position recognition methods currently used, and finally make a summary and outlook on the rigid fruit and vegetable picking robot from the structural development and position recognition methods. Keywords: picking robot, end-effector, grasping methods, separation methods, under-driven, position recognition methodsDOI: 10.25165/j.ijabe.20231605.8120Citation: Zhao Y X, Wan X F, Duo H X. Review of rigid fruit and vegetable picking robots. Int J Agric & Biol Eng, 2023; 16(5): 1-11.